2019
DOI: 10.1109/access.2019.2914232
|View full text |Cite
|
Sign up to set email alerts
|

Radar Moving Target Detection in Clutter Background via Adaptive Dual-Threshold Sparse Fourier Transform

Abstract: In this paper, an adaptive dual-threshold sparse Fourier transform (ADT-SFT) algorithm is proposed, which enables the application of the SFT and robust SFT (RSFT) to the moving target detection in clutter background. Two levels of detection are introduced in this algorithm. First, a scalar constant false alarm rate (CFAR) detection is employed in each frequency channel formed by subsampled fast Fourier transform (FFT) to suppress the influence of strong clutter points on the sparsity and frequencies estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Therefore, in the background of the low SCR, the performance of the SFRFT algorithm will deteriorate, which will easily lead to false alarms. We combine the novelty of ADT-SFT in [27], and proposed the robust SFRFT (RSFRFT) [33], shown in Fig. 1, which is composed of seven procedures.…”
Section: B the Second Stage Detection Via Sparse Fractional Represenmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the background of the low SCR, the performance of the SFRFT algorithm will deteriorate, which will easily lead to false alarms. We combine the novelty of ADT-SFT in [27], and proposed the robust SFRFT (RSFRFT) [33], shown in Fig. 1, which is composed of seven procedures.…”
Section: B the Second Stage Detection Via Sparse Fractional Represenmentioning
confidence: 99%
“…7. The N 2 ∈ [2, N ] sampled pulses of the same rangebin in the output of the first stage are performed FRFT and FRAF operations under different transform angle conditions, i.e., (27) where α ∈ (−π, π] is the rotation angle, and τ 0 is a constant indicating the delay, which is determined by the initial distance r 0 of the target to be detected, i.e., τ 0 = 2r 0 /c, K α (t m , u) represents the kernel function.…”
Section: B Detection Comparisons With Frft-fraf-hcimentioning
confidence: 99%
See 1 more Smart Citation
“…Its existence seriously interferes with the detection and tracking performance of radar targets on the sea surface These methods mainly involve the combination of traditional moving target detection (MTD) and adaptive detection technology, among which, space-time adaptive processing (STAP) [14] and constant false alarm rate (CFAR) detection are classic methods of clutter suppression and target detection, respectively, and many results have achieved the detection of large-size and high-strength targets [15]- [18]. For example, Yu et al [19] proposed an adaptive dualthreshold sparse Fourier transform (ADT-SFT) algorithm, and experiments demonstrated that the ADT-SFT algorithm is more suitable for the clutter background and can obtain a better detection performance than SFT and robust SFT. Magraner et al [20] presented a new technique based on cellaveraging CFAR detection, and it achieved good detection results.…”
Section: Introductionmentioning
confidence: 99%
“…The radar target detection research group from Naval Aviation University proposed several SFT-based moving target detection methods, i.e., adaptive dual-threshold sparse Fourier transform (ADT-SFT) [26] and robust SFRFT (RSFRFT) [27], which are more suitable for moving target detection in the clutter background. For highly maneuvering target detection, sparse fractional ambiguity function (SFRAF) [28] can not only achieve good aggregation of high-order phase signals by FRAF, but also achieve effective improvement of computational efficiency, and can realize rapid extraction of maneuvering targets under large data conditions.…”
mentioning
confidence: 99%